Quantitative and molecular analyses of agronomic traits in cassava (Manihot esculenta Crantz) - Ojulong, Henry Fred (University of the Free State, 2006)
Diallel crosses were evaluated in three agro-ecologies in Colombia and parents and families selected for conventional and molecular breeding trials conducted during the study. At the same time an inter-specific cross was evaluated for the effective introduction of higher DMC from wild cassava relatives. High positive and negative GCA and SCA values were estimated for the agronomic yield traits. Harvest index and DMC were under the influence of additive gene action, while ComRt, FRY and DRY were more influenced by non-additive effects. Moderate to high heritability estimates were obtained for the different agronomic traits. High heritability values were estimated for DRY, FRY, DMC, HI, RtPlt and moderate for RtWt. AMMI analysis ranked FRY, DRY, HI and RtPlt as stable, DMC relatively stable and RtWt as unstable across environments. In the seedling stage DRY, FRY, RtWt, and ComRt ranked parents in the same direction. Dry matter content and HI ranked parents similar but in the opposite direction for other yield characteristics. Overall rating ranked MPER 183 and CM 4574-7 as best parents followed by SM 1565-15 and SM 1665-2. Seedling nursery and the diallel analysis identified SM 1741-1 and MPER 183 as good parents for a number of traits. Replication and blocking during clonal evaluation greatly reduced the non-genetic factors resulting in high correlation among traits evaluated. Fresh root yield, DMC, HI, RtWt and RtPlt were found to be important in determining DRY. Root weight was found to be the most important indicator of DRY. Crossing of the elite cultivar MTAI-8 to the wild relative M. tristis resulted in high DMC values ranging from 34.39% to 42.73%. Bulk segregant analysis showed that parent SM 1741-1 was associated with favourable QTLs for DMC. Markers SSRY 150 (R2=18.1%) and SSRY 160 (R2=28.9%) in the diallel cross, SSRY 99 (R2=22.68), SSRY 141 (R235.89) and NS 169 (R2=20.01) in the wild cross and SSRY 11 (R2=34.57), SSRY 62 (R2=50.21) and NS 644 (R2=29.09) in the mapping population showed association with DMC with values high enough for practical use in a MAS breeding programme.

Dialleel kruisings is in drie agro-ekologiese areas in Kolombië geëvalueer en ouers en families is vir konvensionele en molekulêre telingseksperimente geselekteer vir hierdie studie. Terselfdertyd is ‘n inter-spesifieke kruising vir die effektiewe oordrag van droë materiaal opbrengs gene geëvalueer. Hoë positiewe en negatiewe algemene en spesifieke kombineervermoë waardes is vir agronomiese opbrengs eienskappe gevind. Oesindeks (OI) en droë materiaal opbrengs (DMO) was onder invloed van additiewe geenaksie, terwyl kommersiële wortels, vars en droë wortelopbrengs meer deur nie-additiewe geeneffekte beheer is. Gemiddeld tot hoë ooreflikheidswaardes is vir die verskillende agronomiese eienskappe gevind. Hoë oorerflikheid is vir droë en vars wortelmassa, DMO, OI en wortels per plant en gemiddelde oorerflikheid vir wortelmassa gevind. AMMI analise het vars en droë wortelopbrengs, OI en wortels per plant as stabiel geklassifiseer, DMO relatief stabiel en wortelgewig as onstabiel oor omgewings. In die saailingfase was ouers vir droë en vars wortelopbrengs, wortelmassa en kommersiële wortels ongeveer in dieselfde rangorde. Vir DMO en OI was ouers se rangordes weer ongeveer dieselfde, maar in die teenoorgestelde rigting as vir die ander opbrengseienskappe. In die geheel was MPER 183 en CM 4574-7 die beste ouers, gevolg deur SM 1565-15 en SM 1665-2. Die saailingkwekery en dialleel analise het SM 1741-1 en MPER 183 as goeie ouers vir ‘n aantal eienskappe geïdentifiseer. Herhaling en blokke tydens klonale evaluasie het die effek van nie-genetiese faktore grootliks verminder wat tot hoë korrelasies tussen die eienskappe wat geëvalueer is gelei het. Vars wortelopbrengs, DMO, OI, wortelmassa en wortels per plant was belangrik in die bepaling van droë wortel opbrengs. Wortelmassa was die belangrikste faktor in bepaling van droë wortel opbrengs. 190 Die kruising van die elite cultivar MTAI-8 met die wilde tipe M. tristis het tot hoë DMC waardes gelei wat tussen 34.39% en 42.73% gewissel het. Massa segregerende analise het getoon dat ouer SM 1741-1 met goeie kwantitatiewe eienskap lokusse vir DMO geassosieer is. Merkers SSRY 150 (R2=18.1%) en SSRY 160 (R2=28.9%) in die dialleel kruis, SSRY 99 (R2=22.68), SSRY 141 (R235.89) en NS 169 (R2=20.01) in die wilde kruising en SSRY 11 (R2=34.57), SSRY 62 (R2=50.21) en NS 644 (R2=29.09) in die karteringspopulasie het ‘n groot genoeg assosiasie met DMC aangetoon om dit prakties bruikbaar te maak in ‘n merker ondersteunde teelprogram.
Thesis (Ph.D. (Plant Sciences: Plant Breeding))--University of the Free State, 2006
Keywords: Interspecific cross; Clonal evaluation; Seedling nursery; Diallel analysis; Molecular markers; SSR; Cassava -- Breeding -- Colombia; Genetic markers; Cassava -- Clones -- Variation; Stability